Evaluasi Efisiensi Air Gedung Perkantoran Pada Musim Kering Pada Perencanaan Bangunan Gedung Hijau - Mardiaman, Mardiaman; Victorio Siahaan, Tirto Amsal (Universitas Batanghari Jambi, 2024)
Water is necessary for various human activities. The larger the population, the greater the water consumption. Harnessing rainwater and reusing recycled grey and black water can reduce consumption. Water efficiency needs to be a concern because of the limited availability of water and to maintain limited water availability. Water consumption in buildings for office functions is relatively high. Therefore, office buildings are very important to be designed as environmentally friendly buildings. Water efficiency is a criterion for eco-friendly buildings, more commonly known as green buildings. This research aims to improve water efficiency by utilizing rainwater and recycled water in the Waskita Karya building. The secondary data collection required is at the planning stage. The data collected are water-saving features, rainfall, building area of each floor, site plan, and other relevant data. Water efficiency calculations take into account wet and dry days. On wet days because water comes from rain, and on dry days, the water source is only from PDAM and recycled water. Software issued by the Directorate General of Copyright calculates the water balance. The calculation will result in water savings on dry days. Conventional water consumption amounted to 83,153 lt / day, water source from recycled grey water 29,216 lt / day, black water 14,143 lt / day, efficiency on dry days amounted to 76.8%. This research needs to be implemented so that building owners know their water consumption and can support green building performance and water cost savings.